A New Series of Small Molecular Weight Compounds Induce Read Through of All Three Types of Nonsense Mutations in the ATM Gene - Liutao Du; Michael E. Jung; Robert Damoiseaux; Gladys C. Completo; Francesca Fike; Jin‐Mo Ku; Shareef Nahas; Cijing Piao; Hailiang Hu; Richard A. Gatti (2013)
Chemical-induced read through of premature stop codons might be exploited as a potential treatment strategy for genetic disorders caused by nonsense mutations. Despite the promise of this approach, only a few read-through compounds (RTCs) have been discovered to date. These include aminoglycosides (e.g., gentamicin and G418) and nonaminoglycosides (e.g., PTC124 and RTC13). The therapeutic benefits of these RTCs remain to be determined. In an effort to find new RTCs, we screened an additional ~36,000 small molecular weight compounds using a high-throughput screening (HTS) assay that we had previously developed and identified two novel RTCs, GJ071, and GJ072. The activity of these two compounds was confirmed in cells derived from ataxia telangiectasia (A-T) patients with three different types of nonsense mutation in the ATM gene. Both compounds showed activity comparable to stop codons (TGA, TAG, and TAA) PTC124 and RTC13. Early structure-activity relationship studies generated eight active analogs of GJ072. Most of those analogs were effective on all three stop codons. GJ071 and GJ072, and some of the GJ072 analogs, appeared to be well tolerated by A-T cells. We also identified another two active RTCs in the primary screen, RTC204 and RTC219, which share a key structural feature with GJ072 and its analogs.